2008
DOI: 10.1002/jnr.21755
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone increases astrocytic glutamate uptake and protects astrocytes and neurons against glutamate toxicity

Abstract: Thyroid hormone (T(3)) regulates the growth and differentiation of rat cerebellar astrocytes. Previously, we have demonstrated that these effects are due, at least in part, to the increased expression of extracellular matrix molecules and growth factors, such as fibroblast growth factor-2. T(3) also modulates neuronal development in an astrocyte-mediated manner. In the mammalian central nervous system, excitatory neurotransmission is mediated mainly by glutamate. However, excessive stimulation of glutamate rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 49 publications
0
64
0
1
Order By: Relevance
“…It is well-known that reactive astrocytes develop some characteristics of immature cells, such as the expression of vimentin and BLBP484950515253545556. In addition, BR1 and H9 astrocytes stained for rNMDA and GLT1, which are specific for mature astrocytes5758.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that reactive astrocytes develop some characteristics of immature cells, such as the expression of vimentin and BLBP484950515253545556. In addition, BR1 and H9 astrocytes stained for rNMDA and GLT1, which are specific for mature astrocytes5758.…”
Section: Discussionmentioning
confidence: 99%
“…64,65) T3 enhances the expression levels of astrocytic glutamate transporters (GLAST and GLT-1). 66) Furthermore, thyroid hormones indirectly affect neuronal differentiation and function through their action in astrocytes. For example, it has been observed that T3-primed astrocytes express higher levels of heparan sulfate proteoglycans, which provide neurite outgrowth effects.…”
Section: Organic Anion Transportersmentioning
confidence: 99%
“…A study of rats showed that astrocytes treated with T3 increased mRNA levels and protein expression of the glutamate transporters, glutamate aspartate transporter (GLAST) and glial glutamate transporter-1 (GLT1). This ultimately regulated the extracellular glutamate content [11]. Some studies have shown that autoimmune thyroiditis and type 1 diabetes mellitus (T1DM) used the same antibody as glutamic acid decarboxylase antibodies (GAD-Ab).…”
Section: Discussionmentioning
confidence: 99%